Optical Modeling of Black Carbon With Different Coating Materials: The Effect of Coating Configurations. Issue 23 (11th December 2019) - Luo, Jie; Zhang, Qixing; Luo, Jianfei; Liu, Jia; Huo, Yinuo; Zhang, Yongming
Abstract: In this work, an assembly of coating structures is generated for coated black carbon (BC) based on two different coating methods with limited tunable parameters. By defining typical parameters, the proposed coating structures show great agreement with the detailed morphologies of coated BC particles in the atmosphere. Our models can accurately reproduce the measured linear backscattering depolarization ratio (LDR). We noticed that BC with spherical coatings (Configuration E) has difficulty estimating large LDRs, while the ability to reproduce a large LDR is improved by making the coating structure slightly nonspherical (Configuration C). Our models also show a better performance in reproducing the laboratory‐measured absorption enhancement ( E abs ), mass absorption/scattering cross sections, and absorption Ångström exponent than the simplified models. In addition, sizable uncertainties in the optical properties of coated BC with different coating configurations are found. The uncertainties in the LDR, E abs, mass absorption cross section, and absorption Ångström exponent caused by the coating configurations can reach approximately 220%, 35%, 90%, and 20%, respectively. Therefore, complex coating structures should be carefully considered. In this work, various coating structures are represented by limited tunable parameters, which is beneficial to the parameterization of the optical properties of BC with a complex coating structure. Our models can also provide tools for exploring the agreement between calculations and measurements. Key Points: Various morphologically realistic coated black carbon structures are generated based on two coating methods with limited tunable parameters The generated structures show great agreement with the real morphologies of coated black carbon Our models show excellent performance when reproducing the measured linear backscattering depolarization ratio and other optical parameters